Simulation of Subject Coordination for a Smart Campus Based on Complex Network and Evolutionary Game Theory. (26th June 2022) - Guo, Shaoyong; Pang, Ting
Abstract : The construction of smart campuses can help realize the modernization of higher education. However, the subjects and mechanisms are easily ignored in the construction of smart campuses in colleges and universities. The purpose of this paper is to construct an evolutionary game model based on the complex network structure characteristics of smart campus subjects and the dynamic relationship of collaborative games. Taking the scale-free network as the carrier, the decision-making behavior among subjects is explained. Then, the importance of subject coordination and the effectiveness of the mechanisms of leadership organization, special funds, assessment rewards, and punishments are analyzed through the simulation platform, i.e., Simpy. The results show that (1) moderate subject collaboration helps to avoid the phenomenon of getting something for nothing, (2) appropriate leadership and organization mechanisms can promote the construction process, (3) special fund mechanisms can ensure sustainable development, and (4) assessment reward and punishment mechanisms can increase the popularity of achievements. The proposed method enriches relevant theories of smart campus research and provides a reference for decision-making in smart campus construction.